THE EXPERIENCE OF PHYSIOTHERAPY TREATMENT OF VESICO-DEPENDENT FORMS MEGAURETER IN CHILDREN - S. P. Jatsyk; B. K. Shamov; I. E. Smirnov; S. M. Sharkov; O. M. Konova; A. G. Burkin (Педиатрическая фармакология)
The article reflects one of the important challenges in pediatric urology — treatment of megaureter in children, the condition which can lead to sclerotic changes in renal parenchyma and development of chronic renal failure. The authors used the physiotherapeutic method of treatment, including electrophoresis with the anti-sclerotic agent at the area of bladder and lower third of ureters. The received results, demonstrating successful effect of this treatment, are represented in the article.